手のメンタルローテーション課題が小指外転筋に対応する脊髄前角細胞の興奮性に与える影響: 注視課題による検討 - 前田, 剛伸; 鈴木, 俊明; 栁川, 洸輔 (関西理学療法, 2021)
In the hand mental rotation (MR) task, an image of the hand is presented, and the subject judges whether the hand shown is the right or left by mentally rotating and converting the image. The reaction time and correct answer rate are then measured. This study aimed to determine the effect of the difference in viewpoints of the hand MR task on the excitability of the spinal anterior horn cells of the abductor digiti minimi muscle using F-wave measurements. The subjects were 12 healthy adults (age [mean ± standard deviation]: 23.8 ± 4.2 years). We used the task of viewing the thumb and the little finger. The F-waves were measured at rest and during the tasks of viewing the thumb and the little finger. The changes in F-wave persistence and F/M amplitude ratio between rest and during each task were compared. F-wave persistence and the F/M amplitude ratio were higher during the respective tasks of viewing the thumb and the little finger than at rest, and the F-wave persistence and F/M amplitude ratio were higher during the task of viewing the little finger than during the task of viewing the thumb. These findings suggest that viewing at the corresponding point (the little finger) may further increase the excitability of the spinal anterior horn cells of the abductor digiti minimi muscle.